2022
DOI: 10.1520/jte20200483
|View full text |Cite
|
Sign up to set email alerts
|

A New Low-Activity Nuclear Density Gauge for Soil Density Measurements

Abstract: For decades, nuclear density gauges have been used to measure the density and moisture content of soil during compaction testing in road and embankment construction. Worldwide regulatory agencies consider nuclear density gauges as controlled devices because of their inclusion of radioisotope sources. Regulatory requirements, such as the need for licensing, special storage, special transportation procedures, gauge operator training, and personal dosimetry, have become burdens for gauge users. Recently, a new nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A literature review on the use of LANDG has shown quite promising results. Troxler Electronic Laboratories evaluated the precision and repeatability of the LANDG at road construction projects in Roxboro, Wayne County, and eight other road construction projects in North Carolina in a variety of soil types (2). Their results indicated that the LANDG showed a high correlation to the NDG.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A literature review on the use of LANDG has shown quite promising results. Troxler Electronic Laboratories evaluated the precision and repeatability of the LANDG at road construction projects in Roxboro, Wayne County, and eight other road construction projects in North Carolina in a variety of soil types (2). Their results indicated that the LANDG showed a high correlation to the NDG.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Troxler Electronic Laboratories incorporated a low-activity gamma ray source (strength less than 3.7 MBq, 0.1 mCi) in a device known as the EGauge (ASTM D8167). Generically called a low-activity NDG or LANDG, it utilizes a gamma ray source to measure soil density that is exempt from NRC licensing in the U.S.A. and its territories (2). Moisture content is obtained using a separate device that accompanies the LANDG by measuring the dielectric constant of the soil between the top and bottom of a soil probe.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It permitted the development of nuclear density gauges that use extremely low-activity radioisotope sources. As a result, in this configuration, these devices were recently declared exempt from licensing and other nuclear regulatory requirements, for instance, in the United States (Dep et al, 2021).…”
Section: Soil Neutron Gauge Technique and Usagementioning
confidence: 99%